2021
DOI: 10.1063/5.0055028
|View full text |Cite
|
Sign up to set email alerts
|

Properties of higher-order surface acoustic wave modes in Al1−xScxN/sapphire structures

Abstract: In this work, surface acoustic wave (SAW) modes and their dependence on propagation directions in epitaxial Al0.68Sc0.32N(0001) films on Al2O3(0001) substrates were studied using numerical and experimental methods. In order to find optimal propagation directions for higher-order SAW modes, phase velocity dispersion branches of Al0.68Sc0.32N on Al2O3 with Pt mass loading were computed for the propagation directions <112¯0> and <11¯00> with respect to the substrate. Experimental inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It would also be interesting to see the effect of the morphological anisotropy on the propagation of SAW waves along different propagation directions. Some preliminary work [ 54 ] has already been carried out on films grown within the group in studying the influence of propagation direction on the SAW resonator characteristics. That study demonstrated that there is no significant influence of propagation direction for AlScN(0001) films grown on sapphire(0001) due to the isotropic nature of the films.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to see the effect of the morphological anisotropy on the propagation of SAW waves along different propagation directions. Some preliminary work [ 54 ] has already been carried out on films grown within the group in studying the influence of propagation direction on the SAW resonator characteristics. That study demonstrated that there is no significant influence of propagation direction for AlScN(0001) films grown on sapphire(0001) due to the isotropic nature of the films.…”
Section: Discussionmentioning
confidence: 99%
“…If the minimal achievable SAW wavelength is larger or of the order of the film thickness, such that the SAW displacement field penetrates deeply into the substrate, the elastic properties of the substrate as well as its orientation (e.g., off-cut angles) have to be known to a high precision. On the other hand, if the frequency range can be considerably extended to higher values, higher-order guided acoustic modes can be used in addition to the lowest SAW to gain information about the elastic moduli of the film [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity analysis in [ 17 ] confirms that the piezoelectric constants have a very small influence on the SAW dispersion curves if compared to the elastic constants. However, depending on the required accuracy in the determination of the elastic moduli, auxiliary measurements with an alternative technique, such as the resonator method [ 10 , 11 ] will be needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation